Acute demands and recovery from common interval training protocols - Elmer, D. J.; Barron, E. N.; Chavez, J. L. (The Journal of Strength and Conditioning Research, 2021)
The definition of interval training is quite broad, with no accepted procedure for classifying protocols with different workloads and work and recovery interval times. In addition, little is known about the differences in training load and recovery from common interval protocols. The purpose of this study was to evaluate the differences in acute physiological demands and perceived difficulty between 3 common interval training protocols and a moderate, continuous exercise session. Eight subjects completed the training sessions on a cycle ergometer in a randomized order, with at least 1 week between sessions: 30-second/4-minute, 1-minute/1-minute, 4-minute/3-minute, and a 45-minute continuous session. Metabolic variables were measured throughout exercise and 30 minutes of recovery. Training impulse (TRIMP), session-RPE, and RPE-training load were also measured. There were significant differences between protocols, including between interval training protocols, for average VO2 (p < 0.001) and heart rate (HR) (p = 0.02), total O2 consumption (p < 0.001), peak lactate (p < 0.001), TRIMP (p = 0.02), session-RPE (p = 0.01), and RPE-training load (p < 0.001). There were no significant differences between interval training protocols for peak VO2 or peak HR attained during exercise. There were also no differences in VO2 or HR after 5 or 30 minutes of recovery. Blood lactate was only significantly higher after 30 minutes of recovery from the 30-second/4-minute compared with the 4-minute/3-minute protocol (p = 0.001) and the 45-minute session (p < 0.001). These findings show a range of differences in acute physiological demands and perceptions from interval training protocols, which should be accounted for when planning training sessions or research studies or when interpreting past research.